Issues and challenges for systematic reviews in indigenous health. Issue 7 (8th December 2009) - McDonald, E; Priest, N; Doyle, J; Bailie, R; Anderson, I; Waters, E
Abstract : This essay outlines key issues raised during a project that aimed to (1) identify the gaps in the international evidence base of systematic reviews of intervention effectiveness relevant to public health decision making to address health inequalities experienced by indigenous people, and (2) identify priority areas and topics for future reviews. A number of indigenous researchers and clinicians invited to participate in the project expressed reservations about the appropriateness and value of conventional systematic reviews of intervention evidence to indigenous health. Ensuring that systematic review methods for indigenous health research meet the needs of those that use them, including indigenous communities themselves, needs to be a key area of ongoing work. The public health group within the Cochrane Collaboration has recognised this as a priority area and initiated exploration of these issues.